Regional Markets for Residential Real Estate: Budget Mechanisms for the Implementation of Antimonopoly Measures (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article considers the features of the conjuncture on the regional markets of residential real estate, analyzes budgetary mechanisms for the implementation of antimonopoly measures, identifies the main shortcomings of the functioning of the regional housing markets, identifies the factors that influence the formation of the price of housing objects in the regional real estate market, it is proved that in Ukraine has a low level of security and affordability of housing for residents of the region, it is determined that one of the main tasks of the formation of the real estate market infrastructure is the creation of a single unit about information space and ensuring its informational openness.
Keywords: regional residential real estate markets, housing markets, demand, supply, market conditions, competition, antimonopoly measures